THÀNH PHẦN LOÀI THÚ NHỎ (BỘ RODENTIA VÀ BỘ INSECTIVORA) Ở VƯỜN QUỐC GIA CHƯ MOM RAY - A.V., Abramov; Trần, Quang Tiến; Nguyễn, Quốc Khánh (Tạp chí Khoa học và Công nghệ nhiệt đới, 2025)
SPECIES COMPOSITION OF SMALL MAMMALS (RODENTIA AND INSECTIVORA) IN CHU MOM RAY NATIONAL PARK The studies on small mammals in the Chu Mom Ray national park in 2014 have found about 55 species among which 45 species belong to Rodentia including 5 families and 19 genus and 10 species belong to Insectivora including 2 families and 6 genus. This research has added 11 species to the animal checklist of Chu Mom Ray national park including 8 rodents and 3 insectivorous species. The rodent species are: Berylmys bowersi, Leopoldamys herberti, Leopoldamys revertens, Niviventer huang, Niviventer langbianis, Niviventer niviventer, Niviventer tenaster, Tamiops maritimus and the insectivorous species are: Chimarrogale varennei, Crocidura tanakae, Crocidura phanluongi.